Cathepsin B-dependent glycolysis contributes to reduced renal uric acid excretion in hyperuricemia - Huagang Lin; Linjing Nie; Deping Wu; Dexian Zhang; Rui Peng; Sijie Tao; Zhibin Ye; Sibo Zhu; Maoqing Ye; Jing Xiao (Communications Biology)
Abstract Decreased renal uric acid excretion is a major contributor to hyperuricemia (HUA), but its underlying mechanism remains unclear. Here, we identify cathepsin B (CTSB) as a key regulator of urate handling in HUA. Urinary CTSB levels were elevated in HUA patients, and renal CTSB expression was increased in HUA mice. In CTSBtecKOmice, the expression of reabsorptive urate transporters URAT1 and GLUT9 was decreased, while the secretory transporter ABCG2 was upregulated, leading to enhanced renal uric acid excretion and reduced serum uric acid (SUA). CTSB deficiency also reduced serum IL-1β, IL-6, and TNF-α levels. In vitro and transcriptomic analyses revealed that CTSB inhibition suppressed glycolysis—marked by reduced HK2 and PKM2 expression—downregulated URAT1 and GLUT9, and upregulated ABCG2. Conversely, CTSB overexpression enhanced glycolysis and reversed these effects. These findings suggest that CTSB promotes urate retention via glycolysis and may serve as a novel target for HUA treatment.